2020
DOI: 10.3390/jpm10030093
|View full text |Cite
|
Sign up to set email alerts
|

Amerindian Ancestry Influences Genetic Susceptibility to Chronic Obstructive Pulmonary Disease

Abstract: The contribution of genetic ancestry on chronic obstructive pulmonary disease (COPD) predisposition remains unclear. To explore this relationship, we analyzed the associations between 754,159 single nucleotide polymorphisms (SNPs) and risk of COPD (n = 214 cases, 193 healthy controls) in Talca, Chile, considering the genetic ancestry and established risk factors. The proportion of Mapuche ancestry (PMA) was based on a panel of 45 Mapuche reference individuals. Five PRDM15 SNPs and two PPP1R12B SNPs were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…A total of 36 GWASs were included for full-text assessment ( Figure 1 ), but most of them were excluded for not/not directly about the etiology of COPD. The P value of 3 GWASs did not meet the threshold of 5 × 10 −8 [ 18 20 ], and in another 4 GWASs there was a lack of replication phases [ 21 24 ]. At last, 5 GWASs met the criteria for inclusion and reported 32 SNPs in or near 25 genes [ 25 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 36 GWASs were included for full-text assessment ( Figure 1 ), but most of them were excluded for not/not directly about the etiology of COPD. The P value of 3 GWASs did not meet the threshold of 5 × 10 −8 [ 18 20 ], and in another 4 GWASs there was a lack of replication phases [ 21 24 ]. At last, 5 GWASs met the criteria for inclusion and reported 32 SNPs in or near 25 genes [ 25 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…One report evaluated the ancestral genetic contribution and SNPs associated with the risk of COPD in a Latin American population characterized by a higher proportion of European ancestry (55.93% ± 6.89) and Mapuche ancestry (35.11% ± 8.54); in this study, the authors reported alleles in PRDM15 associated with protection against COPD and SNPs in PPP1R12B associated with susceptibility [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to DNA quality control, samples were genotyped using the Illumina Global Screening Array [ 60 ], which enabled genotyping of 754,159 genomic markers. We assessed the distribution of DMET variants considering the genetic ancestry, which was previously described and calculated [ 59 , 61 ]. After that, we compared the genotype frequencies in the Chilean population from Talca with those of five major populations from the 1000 Genomes Project ( , accessed on 1 March 2022) [ 8 ]: African, Amerindian, East and South Asian, and European.…”
Section: Methodsmentioning
confidence: 99%